Same-day discharge vs. overnight stay following catheter ablation for atrial fibrillation: a comprehensive review and meta-analysis by the European Heart Rhythm Association Health Economics Committee - Zylla, Maura Magdalena; Imberti, Jacopo F; Leyva, Francisco; Casado-Arroyo, Ruben; Braunschweig, Frieder; Pürerfellner, Helmut; Merino, José L; Boriani, Giuseppe (Europace, 2024)
Same-day discharge (SDD) after catheter ablation of atrial fibrillation (AF) may address the growing socio-economic health burden of the increasing demand for interventional AF therapies. This systematic review and meta-analysis analyses the current evidence on clinical outcomes in SDD after AF ablation compared with overnight stay (ONS).A systematic search of the PubMed database was performed. Pre-defined endpoints were complications at short-term (24-96 h) and 30-day post-discharge, re-hospitalization, and/or emergency room (ER) visits at 30-day post-discharge, and 30-day mortality. Twenty-four studies (154 716 patients) were included. Random-effects models were applied for meta-analyses of pooled endpoint prevalence in the SDD cohort and for comparison between SDD and ONS cohorts. Pooled estimates for complications after SDD were low both for short-term [2%; 95% confidence interval (CI): 1-5%; I2: 89%) and 30-day follow-up (2%; 95% CI: 1-4%; I2: 91%). There was no significant difference in complications rates between SDD and ONS [short-term: risk ratio (RR): 1.62; 95% CI: 0.52-5.01; I2: 37%; 30 days: RR: 0.65; 95% CI: 0.42-1.00; I2: 95%). Pooled rates of re-hospitalization/ER visits after SDD were 4% (95% CI: 1-10%; I2: 96%) with no statistically significant difference between SDD and ONS (RR: 0.86; 95% CI: 0.58-1.27; I2: 61%). Pooled 30-day mortality was low after SDD (0%; 95% CI: 0-1%; I2: 33%). All studies were subject to a relevant risk of bias, mainly due to study design.In this meta-analysis including a large contemporary cohort, SDD after AF ablation was associated with low prevalence of post-discharge complications, re-hospitalizations/ER visits and mortality, and a similar risk compared with ONS. Due to limited quality of current evidence, further prospective, randomized trials are needed to confirm safety of SDD and define patient- and procedure-related prerequisites for successful and safe SDD strategies.